Analisis Formalin dan Asam Salisilat pada Ikan Asin yang dijual di Beberapa Pasar di Bandar Lampung - Auli, Winni Nur; Al Iman, Arif; Fadhila, Safira Cahya; Firmansyah, Arya Kurnia; Gacatorina, Alfiraza; Saputra, Chandra Prayoga; Wijayanti, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2023)
The use of prohibited food additives in the community is a concern due to insufficient education and supervision. Some of them are formalin and salicylic acid in salted fish which is used to extend shelf life. The prohibition on them is due to their damage effects on health. The market in Bandar Lampung is one of the routine selling places for salted fish where it is necessary to study the use of formalin and salicylic acid. The analysis was carried out by random sampling using 5 different salted fish from 5 different markets in Bandar Lampung including Rajabasa, Way Halim, Way Kandis, Korpri, and Gintung market. The analytical method was carried out based on the formation of a redox reaction with KMnO4 for formalin and a complexation reaction of salicylic acid with FeCl3. The results of the analysis showed that one of the WK code samples contained formalin and one of the WH code samples contained salicylic acid. These results indicate that the use of prohibited food additives is still being used by salted fish producers in Bandar Lampung. Supervision and education from various parties, especially in the field of regulation, are very urgent to do.